Post-infarction ventricular septal defect repair: cardioplegic arrest vs. on-pump beating-heart strategy—ten years of experience - Kaemmel, Julius; Pitts, Leonard; Wert, Leonhard; Knosalla, Christoph; Pasic, Miralem (Frontiers in Cardiovascular Medicine, 2025)
BackgroundPost-infarction ventricular septal defect (VSD) repair is in general performed on a cardioplegic heart. An alternative concept is VSD repair on a beating heart. Aim of the study was to identify possible differences in survival between the two strategies.MethodsThe study was a retrospective, observational, single-centre cohort study of data from all patients who underwent post-infarction VSD repair at our institution between May 2012 and December 2022. VSD repair was performed either on an arrested heart with aortic cross-clamping [n = 28 (conventional subgroup)] or on a beating-heart [n = 18 (beating-heart subgroup)] using CPB without aortic cross-clamping. Primary end-point was survival at 1 year after surgery. Secondary endpoints included the analysis of perioperative variables, 30-day mortality and long-term survival.ResultsForty six consecutive patients underwent repair of post-infarction VSD (28 in the “conventional subgroup” and 18 in the “beating-heart subgroup”). The mean age of the patients was 66.4 ± 11.2 years and 63% were men. All-cause mortality during the first postoperative 30-days occurred in 12 of 28 patients (43%) in the “conventional subgroup” and in 4 of 18 patients (22%) in the “beating-heart subgroup”). Survival at one and five years was 34% and 27% for the “conventional subgroup”, compared to 72% and 61% for the “beating-heart subgroup”, respectively [hazard ratio, 2.3; 95% confidence interval (CI), 1.1–4.8; P = 0.0364].ConclusionsThe modified surgical approach performing VSD-repair on a beating heart was associated with a lower risk of postoperative death than the conventional surgical strategy.